133k views
5 votes
What’s the answer need it ASAP

What’s the answer need it ASAP-example-1
User Sophonias
by
6.0k points

1 Answer

2 votes

Answer:

The pair of solutions are
(-2,-1) \ and\ (3,14)

Explanation:


1)y=x^2+2x-1\\2)y-3x=5

Solving for
y in equation 2.


y-3x=5

Adding
3x both sides.


y-3x+3x=5+3x


y=5+3x

Substituting value of
y in equation 1.


5+3x=x^2+2x-1\\

Simplifying it further. Subtracting
5 from both sides.


5+3x-5=x^2+2x-1-5\\


3x=x^2+2x-6\\

Subtracting
3x both sides.


3x-3x=x^2+2x-6-3x\\


0=x^2-x-6\\

Now we have a quadratic equation to solve.


x^2-x-6=0

Solving quadratic by factor method.

Splitting the middle term into two terms
mx \ and\ nx such that
mx+nx=-x \ and (mx)(nx)=-6x^2

By factoring 6 we can get the terms.


mx=-2x \ and\ nx=3x As we know
[2x-3x=-x \ and\ (2x)(-3x)=-6x^2]

So, the equation would be


x^2+2x-3x-6=0

Now, we factor in pairs.

Taking
x as common factor from first two terms and taking
-3 common from last two terms.


x(x+2)-3(x+2)=0

Taking
(x+2) as common factor from the whole.


(x+2)(x-3)=0

The roots can be written as:


x+2=0 \ and\ x-3=0

Solving for
x from the above we get


x=-2 \ and\ x=3

Plugging the values of
x in the equation
y=5+3x

When
x=-2


y=5+3(-2)


y=5-6


y=-1

So
(-2,-1) is one solution.

When
x=3


y=5+3(3)


y=5+9


y=14

So
(3,14) is another solution.

User Davidson
by
5.7k points